2005
DOI: 10.1103/physrevlett.95.207201
|View full text |Cite
|
Sign up to set email alerts
|

Self-Trapping of Magnetic Oscillation Modes in Landau Flux-Closure Structures

Abstract: We investigated the magnetodynamics in rectangular Permalloy platelets by means of time-resolved x-ray photoemission microscopy. 10 nm thick platelets of 16 32 m size were excited by an oscillatory field along the short side of the sample with a fundamental frequency of 500 MHz and considerable contributions of higher harmonics. Under the influence of the oscillatory field, the Néel wall in the initial classical Landau pattern shifts away from the center, corresponding to an induced magnetic moment perpendicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 11 publications
3
43
0
Order By: Relevance
“…Besides the static and quasistatic properties, also the magnetization dynamics in nanopatterned particles has recently attracted considerable interest. [3][4][5] In addition to numerous studies of the influence of nanopatterning on the magnetization in mesoscopic magnetic dots, several studies have also addressed the issue for antidot arrays. While the static magnetic properties of antidot arrays [6][7][8][9] have been studied to a good extent, not much is known about their dynamic properties up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the static and quasistatic properties, also the magnetization dynamics in nanopatterned particles has recently attracted considerable interest. [3][4][5] In addition to numerous studies of the influence of nanopatterning on the magnetization in mesoscopic magnetic dots, several studies have also addressed the issue for antidot arrays. While the static magnetic properties of antidot arrays [6][7][8][9] have been studied to a good extent, not much is known about their dynamic properties up to now.…”
Section: Introductionmentioning
confidence: 99%
“…A similar behavior has been observed for Co/Pt systems 25 . Oscillations due to precessional-like magnetization reversal have been observed in several micrometer-sized thin film structures 26,27,28,29 . In these structures, the zero-field ground state is a flux-closure domain state due to finite-size and demagnetizing field effects, which also have an important influence on the magnetization dynamics.…”
mentioning
confidence: 99%
“…Nembach et al also recently observed a microwave induced reduction of the coercivity for much larger multidomain elliptical Ni 80 Fe 20 elements (160 m 80 m 2 ) [12]. This reduction was explained by an enhanced domain wall nucleation in a microwave field [13] and preferential entropy-driven domain growth in a transverse microwave field [14]. In this Letter we show that for micron-sized single domain magnetic elements the microwave assisted switching is actually based on a coherent motion of the magnetization.…”
mentioning
confidence: 88%